Macrophage activation in stellate ganglia contributes to lung injury-induced arrhythmogenesis in male rats - Hong, Juan (Acta Physiol (Oxf), 2021)
AIM: Patients suffering from acute lung injury (ALI) are at high risk of developing cardiac arrhythmias. We hypothesized that stellate ganglia (SG) neural inflammation contributes to ALI-induced arrhythmia. METHODS: We created an ALI rat model using a single tracheal instillation of bleomycin (2.5 mg/kg), with saline as a sham control. We recorded ECGs by implanted radiotelemetry in male bleomycin and sham rats treated with and without oral minocycline (20 mg/kg/d), an anti-inflammatory drug that inhibits microglia/macrophage activation. The SG neuronal excitability was assessed by electrophysiology experiments. RESULTS: ECG data showed that bleomycin-exposed rats exhibited significantly more spontaneous premature ventricular contractions (PVCs) from 1- to 3-week post-induction compared with sham rats, which was mitigated by chronic oral administration of minocycline. The bleomycin-exposed rats displayed a robust increase in both the number of Iba1-positive macrophages and protein expression of interferon regulatory factor 8 in the SG starting as early at 1-week post-exposure and lasted for at least 4 weeks, which was largely attenuated by minocycline. Heart rate variability analysis indicated autonomic imbalance during the first 2-week post-bleomycin, which was significantly attenuated by minocycline. Electrical stimulation of the decentralized SG triggered more PVCs in bleomycin-exposed rats than sham and bleomycin + minocycline rats. Patch-clamp data demonstrated enhanced SG neuronal excitability in the bleomycin-exposed rats, which was attenuated by minocycline. Co-culture of lipopolysaccharide (LPS)-pretreated macrophages with normal SG neurons enhanced SG neuronal excitability. CONCLUSION: Macrophage activation in the SG contributes to arrhythmogenesis in bleomycin-induced ALI in male rats.